The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/aac.00120-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities and Spectrum of the Novel Fluoroquinolone Lascufloxacin (KRP-AM1977)

Abstract: Lascufloxacin exhibited a broad spectrum of activity against various clinical isolates. Furthermore, lascufloxacin showed the most potent activity against Gram-positive bacteria among the quinolones tested and incomplete cross-resistance against existing quinolone-resistant strains. Enzymatic analysis indicated that lascufloxacin had potent inhibitory activity against both wild-type and mutated target enzymes. These results suggest that lascufloxacin may be useful in treating infections caused by various patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…Altogether, the stable activity of lascufloxacin against first-and second-step mutants of S. pneumoniae was thought to be due to the dual target properties and the inhibition of the mutated enzymes. A recent study indicated that lascufloxacin showed strong activity against S. pneumoniae, including fluoroquinolone-resistant strains, and an enzymatic analysis indicated that lascufloxacin showed potent inhibitory activities against DNA gyrase and topoisomerase IV with mutations in Staphylococcus aureus as well as against those without mutations (15). This report was consistent with our proposal regarding the activity of lascufloxacin.…”
supporting
confidence: 91%
“…Altogether, the stable activity of lascufloxacin against first-and second-step mutants of S. pneumoniae was thought to be due to the dual target properties and the inhibition of the mutated enzymes. A recent study indicated that lascufloxacin showed strong activity against S. pneumoniae, including fluoroquinolone-resistant strains, and an enzymatic analysis indicated that lascufloxacin showed potent inhibitory activities against DNA gyrase and topoisomerase IV with mutations in Staphylococcus aureus as well as against those without mutations (15). This report was consistent with our proposal regarding the activity of lascufloxacin.…”
supporting
confidence: 91%
“…Lascufloxacin and the other quinolones have high bioavailability and long plasma half-lives (bioavailability and half-life of lascufloxacin, 96% and 16.1 h; levofloxacin, 99% and 6.9 h; garenoxacin, 92% and 9.8 to 14.2 h; and grepafloxacin, 72% and 11.1 h, respectively) (4,32,33). Although the clinical dose and AUC in free plasma (fAUC) of lascufloxacin were lower than those of the existing quinolones (dosage and fAUC of lascufloxacin, 75 mg and 2.65 g · h/ml; levofloxacin, 500 mg and 33.1 g · h/ml; garenoxacin, 400 mg and 15.0 g · h/ml; and grepafloxacin, 400 mg and 6.35 g · h/ml) (lascufloxacin [in-house data of Kyorin Pharmaceutical Co., Ltd.]) (33), a Ͼ90% clinical efficacy rate was achieved in patients with respiratory tract infections (6).…”
Section: Discussionmentioning
confidence: 99%
“…Lascufloxacin, an 8-methoxyquinolone from Kyorin, is in phase III and shows improved activity for RTIpathogens.Itexertssome activity against MRSA, but with only limited application because of cross-resistance. [338,339] Finafloxacin, an 8-cyanofluoroquinolone from Merlion which is already marketed for the treatment of ear infections,s hows the same spectrum of activity as ciprofloxacin and cross-resistance to it. As aconsequence of its higher activity at lower pH values,itisdeveloped for UTI and kidney infections.…”
Section: Angewandte Chemiementioning
confidence: 99%